Emotionen als Anforderungssituationen in einer kompetenzorientierten Religionsdidaktik - Gennerich, Carsten (Theo-Web, 2015)
RE in Germany is based on the concept of competence. This affords a curriculum based on a systematic classification of demands or problems solved with religious interpretations of self and world. The article proposes to systematize these problem situations using a taxonomy of emotions. Such a starting point of religious learning has several advantages, for example it is open for all students independent of their degree of religiosity. Using the emotion of envy it is first shown that envy combines three interpretation patterns: (1) Giving special value to something what is owned or achieved by another person. (2) Interpreting the own person in the light of a deficit by social comparison with the other person. (3) Interpreting the other person like an enemy. Related to these patterns helpful religious interpretations of self and world were described to cope with envy. The possible contribution of the resulting learning insights for the development of a systematic religious competence is discussed.